2001
DOI: 10.1046/j.1440-1622.2001.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological view of vascular trauma in Western Australia: A 5‐year study

Abstract: The injury patterns emerging from the present study will hopefully help all medical personnel to recognize the potential for vascular injury in a trauma setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 24 publications
11
54
3
1
Order By: Relevance
“…[9][10][11][12][13][14] The proportion of non-transport-related vascular injuries in our study was similar to that reported in the United States and Latin America, [15][16][17][18] but higher than that reported in Europe, Australia and other developing countries. 12,14 Certain factors that may contribute to a sustained high risk of transport-related injuries in Canada are the increasing number of vehicles on the road, variable road infrastructure in rural areas, reduced use of safety precautions and alcohol consumption. 11,19,20 We did not observe a significant decline in the incidence of vascular injuries among older and rural populations.…”
Section: Discussionsupporting
confidence: 79%
“…[9][10][11][12][13][14] The proportion of non-transport-related vascular injuries in our study was similar to that reported in the United States and Latin America, [15][16][17][18] but higher than that reported in Europe, Australia and other developing countries. 12,14 Certain factors that may contribute to a sustained high risk of transport-related injuries in Canada are the increasing number of vehicles on the road, variable road infrastructure in rural areas, reduced use of safety precautions and alcohol consumption. 11,19,20 We did not observe a significant decline in the incidence of vascular injuries among older and rural populations.…”
Section: Discussionsupporting
confidence: 79%
“…This goes in hand with some of the other studies which show that popliteal artery is the most common injured structure in lower limb vascular injuries 16. On the contrary to our findings in Indian patients, according to Gupta et al ., femoral artery is the most common injured structure in lower extremity vascular trauma in Australian population 17. Nevertheless, the limb salvageability percentage in popliteal artery injury group was a mere 25% whereas it was as much as 64% in the femoral artery injury group, showing that the prognosis was much better when the patient had femoral artery injury.…”
Section: Discussionmentioning
confidence: 97%
“…The most common artery-vein combination injury was to the femoral vessels. 10 In 2002, Lakhwani et al looked at 84 patients in Malaysia with RTAs, which accounted for 58% of vascular trauma cases. Primary arterial repair was the most frequently employed surgical procedure (64%), followed by autogenous reverse long saphenous vein repair (17%) and PTFE, in 4%.…”
Section: Discussionmentioning
confidence: 99%